(untitled) (Scientific journal of the Fergana State University, 2023)
The article considers the process of transformation of young people of New Uzbekistan in their political consciousness and culture as a factor of social adaptation. Also, based on empirical data from research on the analysis of the transformational perspective of youth political consciousness and culture, methodological approaches and main trends of the transformational nature of the political consciousness and culture of modern Uzbek Youth are discussed.